Primary orbital neuroblastoma in a 1‐month‐old boy. Issue 1 (February 2014) - Inazawa, Natsuko; Hatakeyama, Naoki; Hori, Tsukasa; Yamamoto, Masaki; Igarashi, Keita; Tadashi, Hasegawa; Ogino, Jiro; Tsutsumi, Hiroyuki; Suzuki, Nobuhiro
Abstract Neuroblastoma is a malignant tumor predominantly occurring in children and usually arising from the adrenal gland or sympathetic ganglia. We describe a neuroblastoma in a 1‐month‐old boy arising from his left orbital cavity. This tumor was refractory to chemotherapy or radiotherapy, requiring enucleation of the left eye for complete removal of the intraorbital tumor. Thereafter, he received high‐dose chemotherapy followed by autologous peripheral blood stem cell transplantation, and has been in complete remission for 3 years. Unlike neuroblastomas arising from the adrenal gland or sympathetic ganglia, primary orbital neuroblastoma may be refractory even in early infancy.